2015
DOI: 10.1158/1541-7786.mcr-15-0141
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Activity of Klotho in Breast Cancer Is Revealed by Structure–Function Analysis

Abstract: Klotho is a transmembrane protein containing two internal repeats, KL1 and KL2, both displaying significant homology to members of the b-glycosidase family. Klotho is expressed in the kidney, brain, and various endocrine tissues, but can also be cleaved and act as a circulating hormone. Klotho is an essential cofactor for binding of fibroblast growth factor 23 (FGF23) to the FGF receptor and can also inhibit the insulin-like growth factor-1 (IGF-1) pathway. Data from a wide array of malignancies indicate kloth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…Recently, Stromberg et al reported the involvement of IGF-1R and the antitumor effects of specific IGF-1R inhibitors in DLBCL tumorigenesis [ 25 ]. Structure-function analysis of Klotho indicated that Klotho could interact with the IGF-1R [ 43 ]. Klotho-induced inhibition of IGF-1R signaling may act as a novel mechanism involved in the development of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Stromberg et al reported the involvement of IGF-1R and the antitumor effects of specific IGF-1R inhibitors in DLBCL tumorigenesis [ 25 ]. Structure-function analysis of Klotho indicated that Klotho could interact with the IGF-1R [ 43 ]. Klotho-induced inhibition of IGF-1R signaling may act as a novel mechanism involved in the development of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…α-Klotho acts as a tumor suppressor by inhibiting insulin/IGF-1 signaling in breast cancer, lung cancer, pancreatic cancer, gastric cancer, liver cancer, colon cancer, and ovarian cancer ( 57 , 59 , 65 , 73 76 ). Overexpression of α-Klotho or treatment with sKl inhibits insulin/IGF-1-mediated downstream effectors IRS-1, Akt1, and ERK1/2 in cancer cells ( 57 , 59 , 65 , 67 , 73 76 ). The tumor suppressive activity has been attributed to its KL1 domain ( 59 , 76 ).…”
Section: Functions and Mechanism Of Action Of Sklmentioning
confidence: 99%
“…Overexpression of α-Klotho or treatment with sKl inhibits insulin/IGF-1-mediated downstream effectors IRS-1, Akt1, and ERK1/2 in cancer cells ( 57 , 59 , 65 , 67 , 73 76 ). The tumor suppressive activity has been attributed to its KL1 domain ( 59 , 76 ).…”
Section: Functions and Mechanism Of Action Of Sklmentioning
confidence: 99%
“…While not impossible to perform our experiments with transfected Klotho plasmids with and without PTCs, it is challenging having to use the large, native 50 kb gene, since splicing is eliminated in cDNA translation. As expected, "secreted Klotho" cDNA leads to protein production for this reason (10,42,43), which is likely nonphysiological, in spite of the biological effects of overexpressed secreted Klotho, essentially amounting to KL1 domain effects (3,(44)(45)(46)(47)(48)(49)(50). Notably, the antibody we used to detect Klotho (KM2076) would detect the KL1 domain in any KL1-containing form of Klotho (13,51).…”
Section: Discussionmentioning
confidence: 67%
“…For example, Lu et al found that ovarian carcinoma patients positive for alternative Klotho mRNA have a higher tumor grade (17), which is interesting in light of the generally accepted view of Klotho as a tumor suppressor (44,46,60,61), including in ovarian carcinoma (62,63). However, higher alternative Klotho expression levels may not implicate effects of Klotho protein in whichever form and may even indicate dysregulated splicing or NMD dysfunction, which would lead to ER stress and may therefore reflect general cellular health.…”
Section: Discussionmentioning
confidence: 99%